KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM MELAKSANAKAN SUPERVISI AKADEMIK - Sumartana Sumartana Sumartana (UNIVERSITAS BENGKULU, 2016)
The purpose of this study is to describe the principal's leadership in implementing learning academic supervision Sindang SD 04 Kelingi Rejang Lebong district. The method used descriptive qualitative research. Subjects were 04 district elementary school principal sindang Kelingi Rejang Lebong. Data collection techniques used were interviews, observation and documentation. The results showed that the elementary school principal learning leadership inimplementing the academic supervision of State 04 Sindang Kelingi Rejang Lebong implement individual supervision and group supervision techniques.Keywords: principal, leadership